Odd Exponential Half Logistic Distribution - Basma M. Zwain, Ahmed AL-Adilee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In this work, we introduce a new distribution, the Odd Exponential Half Logistic Distribution(OEHLD), by expanding the half logistic distribution to boost its adaptability.The survival function, the hazard rate function, the order statistics, the quantiles, the median, and the asymptotic confidence bounds are all derived.After obtaining a new distribution. The new obtained parameters are estimated by using the maximum likelihood estimation (MLE) method to fit the new distribution.To choose the most appropriate distribution for the data, a comparison was performed using goodness-of-fit metrics.